An Alpha-glucosidase Enzyme Inhibitor Cycloeucalenol from Sarcolobus globosus Unveiled through In vitro and Computational Analysis (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Sarcolobus globosus is a medicinal plant grown in the Sundarbans, exhibiting a spectrum of pharmacological properties. This study was devised to scrutinize the potential antidiabetic attributes intrinsic to S. globosus leaves. In the oral glucose tolerance test (OGTT), the extract displayed a dose-dependent reduction in blood glucose levels compared to the standard glibenclamide. The extract also demonstrated a notable suppression of the alpha-glucosidase enzyme (IC50 = 0.407 mg/ml), juxtaposed against the efficacy of the established standard voglibose (IC50 = 0.329 mg/ml). Cycloartane triterpene, identified as cycloeucalenol, was isolated, exhibiting an IC50 of 0.423 mg/ml. Cycloeucalenol was subjected to MD analysis against the protein model (PDB ID: 3A4A), revealing a binding affinity of –9.4 kcal/mol, exceeding that of voglibose (–6.1 kcal/mol), and closely approximating the binding affinity of acarbose (–9.7 kcal/mol). Afterward, cycloeucalenol and acarbose were subjected to MDS studies to explore thermal stability. In addition, an ADMET analysis was performed, affirming the oral bioavailability and safety profile of cycloeucalenol.Dhaka Univ. J. Pharm. Sci. 24(1): 11-28, 2025 (June)